Uncharted Strait : The Future of China-Taiwan Relations - Bush, Richard C., 1947- (Book collections on Project MUSE., 2013)
This book focuses on cross-Strait relations during Ma Ying-jeou's first term, assessing the impact of stabilization on economics, politics, and security and the implications for resolution of Taiwan and China's fundamental dispute. Examines how Taiwan can strengthen itself; how China can promote a mutually acceptable outcome; and how Washington can protect its interests in Asia. -- Provided by publisher.